The Theoretical Description of Sucralose and Lugduname Electrochemical Determination in Beverages - Tkach, V. V.; Morozova, T. V.; Kushnir, M. V.; de Oliveira, S. C.; Odyntsova, V. M.; Krasko, M. P.; Antonyuk, I. Yu.; Hrabovska, O. V.; Fedorova, D. V.; Kormosh, Z. O.; Ivanushko, Y. G.; Melnyk, O. O.; et al. (My University, 2024)
The possibility of sucralose and lugduname electrochemical determination in beverages has been analyzed for the first time from a theoretical point of view. It has been shown that the electrochemical determination of sucralose and lugduname may be carried out efficiently by an anodic process due to the presence of electroactive groups in both substances despite the hybrid mechanism for lugdunam electrooxidation. The stability analysis of the system from the steady-state formation and maintenance point of view confirms that the neutral or mildly acidic medium is favorable for the determination of both sweeteners.
Keywords: sucralose; lugdunam; cobalt (III) oxyhydroxide; conducting polymer; electrochemical sensor; stable steady-state